Development of Microfluidic Paper-Based Analytical Devices for Simultaneous Colorimetric Ammonium and Nitrate Detection - Yucha, Ruangsak; Permpipat, Patcha; Muansuwan, Parintron; Chaianongsak, Rachaphon; Prakobkij, Akarapong; Kitchawengkul, Nattasa; Panseeta, Panomwan (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The frequency of terrorist attacks involving Improvised Explosive Devices (IEDs) is expected to continue increasing. Ammonium nitrate fuel oil (ANFO) is the preferred main charge in IEDs due to its low cost and wide availability. Hence, there is a pressing need to develop an ammonium nitrate detection method that is easy to use, cost-efficient, fast, and reliable. This research developed the µPADs as viable devices for detecting ammonium nitrate in the field alongside a mobile phone camera. In this study, a two-lane µPAD was developed to detect both ammonium and nitrate ions in an ammonium nitrate solution. The purpose of this research was to develop a simple and low-cost colorimetric method for simultaneous ammonium and nitrate ion detection using microfluidic paper-based analytical devices (µPADs) fabricated by the wax-screen printing technique. The two-channel µPADs were designed and fabricated. The first channel was used for ammonium detection using Nessler’s reagent coated on the detection at the end of the channel. The second channel was used for nitrate detection using a Griess reagent. By simply dropping the sample at the center of µPADs, the developed µPADs were able to detect both ammonium and nitrate in a short time (only 4 minutes). The colored product on the µPAD (yellowish-brown and pink color for ammonium and nitrate, respectively) was then captured with a camera on a smartphone under a commercial controlled light box and its color intensity was obtained by using ImageJ software. Using the NH4NO3 concentration in the range of 100 – 800 ppm, under optimum conditions, there was a good linear relationship (r2 = 0.9961 for ammonium concentration range of 200-800 ppm and r2 = 0.9894 for nitrate concentration range of 100-800 ppm) and the detection limit was 48.760 and 81.966 ppm for ammonium and nitrate, respectively.